2014
DOI: 10.2147/vhrm.s45181
|View full text |Cite
|
Sign up to set email alerts
|

Challenges associated with peripheral arterial disease in women

Abstract: Peripheral arterial disease (PAD) is an increasingly recognized disorder that is associated with functional impairment, quality-of-life deterioration, increased risk of cardiovascular ischemic events, and increased risk of total and cardiovascular mortality. Although earlier studies suggested that PAD was more common in men, recent reports based on more sensitive tests have shown that the prevalence of PAD in women is at least the same as in men, if not higher. PAD tends to present itself asymptomatically or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 134 publications
0
30
1
Order By: Relevance
“…Atherosclerotic lower extremity PAD impairs walking performance 77 and is associated with not only a reduced quality of life 78,79 but also a markedly increased risk of CVD events and mortality. 80 Although male sex was traditionally believed to be a risk factor for PAD, recent studies 81,82 have reported compelling results on the high prevalence of PAD in women. At the extremes of ages <40 and >80 years), women represent a greater estimated population burden of PAD, affecting the lower extremities.…”
Section: Peripheral Arterial Disease In Womenmentioning
confidence: 99%
“…Atherosclerotic lower extremity PAD impairs walking performance 77 and is associated with not only a reduced quality of life 78,79 but also a markedly increased risk of CVD events and mortality. 80 Although male sex was traditionally believed to be a risk factor for PAD, recent studies 81,82 have reported compelling results on the high prevalence of PAD in women. At the extremes of ages <40 and >80 years), women represent a greater estimated population burden of PAD, affecting the lower extremities.…”
Section: Peripheral Arterial Disease In Womenmentioning
confidence: 99%
“…Differences between women and men in the etiology and clinical presentation of PAD have also been suggested. 7 However, long-term data on sex-based differences in the cardiovascular and limb outcomes of patients with PAD are limited. Previous population-based studies have focused primarily on postoperative in-hospital outcomes, and their findings have been conflicting.…”
mentioning
confidence: 99%
“…This possibility, however, has been refuted by several studies that showed women tend to be diagnosed later with more advanced forms of PAD. 17,18 …”
Section: Discussionmentioning
confidence: 99%